2013
DOI: 10.1111/eje.12059
|View full text |Cite
|
Sign up to set email alerts
|

Levels of agreement between student and staff assessments of clinical skills in performing cavity preparation in artificial teeth

Abstract: Students tend to overrate the quality of their performance when compared with staff ratings. Task difficulty has an impact on levels of agreement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(77 citation statements)
references
References 15 publications
6
66
2
Order By: Relevance
“…Other studies have also found disagreement between student self-assessments and faculty assessments (10,15,(17)(18)(19). However, unlike our findings, previous research has found that poorly performing students tend to overrate their performance, while high-performing students are more self-critical and tend to underrate it (15,17,18,20). Other studies have found that students are more likely to overestimate their competence than their tutors (10,19).…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies have also found disagreement between student self-assessments and faculty assessments (10,15,(17)(18)(19). However, unlike our findings, previous research has found that poorly performing students tend to overrate their performance, while high-performing students are more self-critical and tend to underrate it (15,17,18,20). Other studies have found that students are more likely to overestimate their competence than their tutors (10,19).…”
Section: Discussioncontrasting
confidence: 99%
“…Tasks 3-5 involved operating on a mandibular first molar situated in the lower jaw: with a small carious lesion (task 3), a carious lesion already in the The previous scoring system used by the faculty for the phantom-head laboratory involved assessing the angle of entry, the hold of the instruments, the area of caries remaining from both the cavity wall and the cavity floor, the avoiding of pulp exposure, and the conservation of healthy tooth structure. 24 For this study, we developed a similar scoring system for hapTEL cavity preparation tasks named the hapTEL Accuracy of Caries Excavation (ACE) score) ( Table 2) to assess the VRS data recorded by the log-files.…”
Section: Methodsmentioning
confidence: 99%
“…26 The quantitative nature of the feedback allows students to monitor their progress objectively and institutions to assess their students for formative or summative exams. 24 Electronic learning assessment methods are encouraged by the Higher Education Students who delayed first contact performed better. 23 This occurred during the hapTEL sessions with one to two tutors circulating amongst the students, reminding them of their educational goals and reinforcing the experience for the longer term biological aims in real patient situations.…”
Section: Figure 2 Distribution Of Overall Accuracy Of Caries Excavatmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] Simulation training using mannequins helps undergraduate students understand the principles or techniques of their respective dental fields. 8,9 In general, however, patients in the oral unit have several dental morbidities. To teach technical skills effectively, existing jaw models focus on specific dental diseases; however, these models cannot replicate the oral conditions of actual patients.…”
mentioning
confidence: 99%